2011
DOI: 10.1039/c1mt00015b
|View full text |Cite
|
Sign up to set email alerts
|

Zinc, copper, and carnosine attenuate neurotoxicity of prion fragment PrP106-126

Abstract: Prion diseases are progressive neurodegenerative diseases that are associated with the conversion of normal cellular prion protein (PrP(C)) to abnormal pathogenic prion protein (PrP(SC)) by conformational changes. Prion protein is a metal-binding protein that is suggested to be involved in metal homeostasis. We investigated here the effects of trace elements on the conformational changes and neurotoxicity of synthetic prion peptide (PrP106-126). PrP106-126 exhibited the formation of β-sheet structures and enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 78 publications
1
43
0
Order By: Relevance
“…These effects may help to explain how dietary carnosine helps to suppress accumulation of b-amyloid in the brains of transgenic mice model for Alzheimer's disease (Corona et al, 2011). Additionally, carnosine has recently been shown to suppress the toxicity of prion protein (Kawahara et al, 2011). This may be due to either carnosine-stimulated prion proteolysis and/or decreased glycolysis (see below), as prion proteins have also been shown to stimulate protein glycoxidation by upregulating glycolysis (Gadwinecka et al, 2010;Li et al, 2011a).…”
Section: Defence Against Mg By An Endogenous Agent Carnosinementioning
confidence: 99%
“…These effects may help to explain how dietary carnosine helps to suppress accumulation of b-amyloid in the brains of transgenic mice model for Alzheimer's disease (Corona et al, 2011). Additionally, carnosine has recently been shown to suppress the toxicity of prion protein (Kawahara et al, 2011). This may be due to either carnosine-stimulated prion proteolysis and/or decreased glycolysis (see below), as prion proteins have also been shown to stimulate protein glycoxidation by upregulating glycolysis (Gadwinecka et al, 2010;Li et al, 2011a).…”
Section: Defence Against Mg By An Endogenous Agent Carnosinementioning
confidence: 99%
“…3). We have also demonstrated that PrP106-126 forms β-sheet structures and exhibits neurotoxicity as well as AβP (Kawahara et al, 2011a). In addition, oligomeric α-synuclein causes neuronal death via the Ca 2+ influx (Danzer et al, 2007).…”
Section: Disruption Of Calcium Homeostasis By Amyloid Channelsmentioning
confidence: 80%
“…All three peptides attenuated Cu 2+ -induced neurotoxicity [51]. Although PrP77-83 and PrP144-157 are not neurotoxic, PrP106-126 forms β-sheet structures during the "aging" process (the incubation at 37°C for several days), as determined using the thioflavin T (ThT) fluorescence assay, far-UV circular dichroism (CD) spectroscopy and atomic force microscopy (AFM) imaging.…”
Section: Metal-induced Conformational Changes Of Prion Protein and Itmentioning
confidence: 99%